The good teacher, the metaphorical tickle trunk, and the survival of the fitter - McLean, Terence (My University, 2018)
While being a good teacher is not getting any easier, pinpointing what good teaching or a good teacher is poses a bit of a conundrum. Of course, well-constructed syllabi, solid subject material, and interesting activities are essential, but what about the teacher? There's the rub. Without the good teacher, the best laid plans can go awry. Good teaching requires a little more; and this, along with the technical side of instruction, is what we need to develop. Survival in any profession requires effort, and good teachers know it. This paper offers the author's opinions as well as a look at literature on post-secondary educators and students' perceptions of good teaching.
Keywords: teaching; professional development; reflection